Value Driven Growth Mindset and Value Driven Fixed Mindset? - Tambun, Toronata; Irawanto, Dodi Wirawan (APMBA (Asia Pacific Management and Business Application), 2023)
This article explores the integration of growth and fixed mindsets with ethical considerations and primal instincts, offering a fresh perspective on understanding human behaviour, especially in studying organizational behaviour. The motivation behind this exploration is to extend Carol Dweck's mindset theory by incorporating moral and instinctual dimensions, addressing a gap in how these mindsets intersect with ethical decision making that motivated behaviour in organization. The primary method involves constructing a 2x2 matrix that categorizes individuals based on their mindset (growth or fixed) and their tendency to either uphold ethical and moral principles or succumb to primal brain stem impulses. This matrix serves as a tool to elucidate the complex interaction between cognitive orientations and ethical or instinctual drives. For the organizational behaviour, these comprehensive framework, highlights the nuanced relationship between mindset typologies and ethical or primal inclinations, proposing that behaviour is a product of this multifaceted interaction in the interaction of individual in organization. The article concludes with insights on how this integrated approach can enhance our understanding of human actions and decision-making processes.